Analisis Dampak Aktivitas Industri Minyak Dan Gas Terhadap Sektor Ekonomi Di Kabupaten Seram Bagian Timur: Analysis of the Impact of Oil and Gas Industry Activities on the Economic Sector in East Seram Regency - Asmiani, Nur; Rahareng, Sutriani; Thamsi, Alam Budiman; Aswadi, Muhammad (Journal of Engineering Science and Technology Applications, 2024)
PT Kalrez Petroleum Seram Ltd is a company engaged in the oil and gas mining sector. The company started operations in 2001 and is part of South Sea Petroleum Holdings Ltd, based in Hong Kong. This study aims to analyze the base sectors that can support economic growth and examine the potential of the mining and quarrying sector in supporting economic development in the region. The data used in this study is secondary data obtained from various related agencies, one of which is the Central Statistics Agency (BPS). The data analyzed includes the Gross Regional Domestic Product (GDP) of Eastern Seram Regency and Maluku Province based on constant prices by business field in the 2011-2020 period. This study uses Location Quotient (LQ) and shift-share analysis methods to identify the base sector and analyze the dynamics of economic growth. The results of the analysis show that the base sectors in this area include the fisheries, forestry, and agriculture sectors with an LQ value of 1.06; mining and quarrying sector with an LQ value of 11.37; real estate services with an LQ value of 1.13; and health services and social activities with an LQ value of 1.07. However, the growth of the value of GDP in the mining sector during the 2011-2020 period experienced a significant decrease, namely -6,323.94 million rupiah. Other growth indicators, namely the Proportional Growth Contribution (KPP) of -0.22 and the Regional Growth Contribution (KPPW) of -0.14, also show that the mining and quarrying sector is relatively slow in growth, although it remains competitive at the regional level. The decline in the value of KPP and KPPW with a negative sign (-) in the mining and quarrying sector confirms that this sector is experiencing suboptimal growth. Although its competitiveness is relatively still there, this persistent decline indicates the need for more attention to improving efficiency and innovation within the sector. This is important so that the mining and quarrying sector can contribute more to improving the regional economy in a sustainable manner. To support the development of this sector, strategic policies, investment in technology, and synergy between the government and industry players are needed to overcome existing challenges